TEACHING SELF-INTRODUCTION BY USING THE WHOLE BRAIN TEACHING METHOD - Fayogi, Silvia Febridian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract:This research investigated the use of Whole Brain Teaching method in teaching self-introduction. Whole Brain Teaching method is a method designed toward maximizing student’s engagement, and focusing on the way the brain is really designed to learn. The seventh grade students were chosen because based on the syllabus that self-introduction is a material for seventh grade students; there are 29 students of Junior High School Bina Kusuma Nanga Pinoh as participants. The type of this research is pre-experimental, that was made to try out the use of the Whole Brain Teaching method in teaching self-introduction. The purposes of doing this research were to investigate the effectiveness and the effect size of using Whole Brain Teaching method in teaching self-introduction.The writer used the measurement technique to collect the data and the tool of data collection was speaking rubric assessment. The data which have been collected are analyzed by using the speaking scoring rubric from Cohen, et al, and modified by the writer. The research found that the use of Whole Brain Teaching method is effective in teaching self-introduction, where tratio=6.17 is higher than tcritical=2.048 and the use of Whole Brain Teaching method gives a strong effect toward the students’ ability in performing self-introduction in English, where ES=1.11. Whole Brain Teaching method can be an alternative solution for teacher to teach the students since it can help the students in comprehending self-introduction. Keywords:Whole Brain Teaching method, Self-introduction Abstrak:Penelitian ini menginvestigasi penggunaan metode Whole Bran Teaching dalam mengajar self-introduction. Metode Whole Brain Teachig adalah metode yang di desain untuk memaksimalkan keikutsertaan siswa, dan focus pada bagaimana otak memang di desain untuk belajar. Siswa kelas tujuh dipilih karena berdasarkan silabus bahwa self-introduction adalah materi untuk siswa kelas tujuh; sebanyak 29 siswa dari Sekolah Menengah Pertama Bina Kusuma Nanga Pinoh yang menjadi peserta. Jenis penelitian ini adalah pre-eksperimental, yang dibuat untuk mencoba penggunaan dari metode Whole Brain Teaching dalam mengajar self-introduction. Maksud dari penelitian ini adalah untuk menginvestigasi efektivitas dan effect size dari penggunaan metode Whole BrainTeaching dalam mengajar self-introduction. Penulis menggunakan measurement technique untuk mengumpulkan data dan alat untuk mengumpulkan data adalah rubrik penilaian berbicara. Data yang telah terkumpul dianalisis menggunakan rubrik penilaian berbicara dari Cohen, dkk, dan dimodifikasi oleh penulis. Penelitian menemukan bahwa penggunaan metode Whole Brain Teaching efektif dalam mengajar self-introduction, dimana tratio=6.17 lebih tinggi dibandingkan tcritical=2.048 dan penggunaan metode Whole Brain Teaching member efek yang kuat untuk kemampuan siswa dalam mempraktikkan self-introduction dalam Bahasa Inggris, dimana ES=1.11. metode Whole Brain Teaching bias menjadi sebuah solusi alternatif untuk guru dalam mengajar siswa karena hal tersebut dapat membantu siswa untuk meningkatkan self-introduction. Kata Kunci: Metode Whole Brain Teaching, Self-introduction